EFEKTIVITAS KOLABORASI MEDIA NEARPOD DAN SMART BOX TERHADAP KEMAMPUAN PEMAHAMAN KONSEP PADA MATERI PENGURANGAN BERSUSUN DI KELAS II SD NEGERI 1 CIGADUNG - Sari, Nia Kurnia; Lousy Loustiawaty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by students' difficulties in understanding the concept of subtraction. The researcher found that the conceptual understanding ability of grade II students at SD Negeri 1 Cigadung was still weak with the condition of students' lack of enthusiasm for learning mathematics and minimal use of learning media in the classroom. The purpose of this study was to determine the effectiveness of the use of nearpod and smart box media collaboration in improving students' conceptual understanding abilities, especially the material on subtraction. This study used a quantitative method using the (Quasi Experimental Design research approach and using the Nonequivalent Control Group Design. The subjects of this study involved two classes as samples in the study, including the experimental class (Class II A) which was learning using nearpod and smart box media collaboration and the control class (Class II B) which was learning conventionally. The instruments in this study consisted of a conceptual understanding ability test sheet and an observation sheet. The analysis techniques used were test instrument tests, prerequisite tests, hypothesis tests using SPSS ver. 27 software. The results showed that students in the experimental class had an average posttest score of 80.96, while the control class only had 58.13. The t-test analysis using the independent sample t-test showed a significant difference between the two classes (P < 0.005). The increase in students’ conceptial undertanding is in the moderate category, as evidenced by the N-gain value. Thus, the use of nearpod and smart box media collaboration has proven effective in improving students' conceptual understanding.